THE EFFECT OF LOCATION, SERVICES, AND PROMOTION ON THE INTEREST OF TOURIST VISITS TO AGRO PURWOSARI, MIJEN DISTRICT, SEMARANG CITY - Juli Kurniawan; Agus Setiadi; Mukson Mukson (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Agro Purwosari is one of the leading agro-tourism in Semarang, managed by the Technical Implementation Unit of the Garden Service of the Semarang City Agricultural Service. The role of visitors is vital for the existence of Agro Purwosari. Factors that can influence visitors' interest include service quality, destination image, tourist attraction, and promotion. This study aims to analyze the effect of service quality, location, and advertising on interest in visiting Agro Purwosari. This research uses quantitative research. The sampling technique in this study used accidental sampling. The number of respondents who were taken in this study was 75 respondents. The results of the logistic regression test prove that the quality of service has a positive and significant effect on the interest in visiting Agro Purwosari with the regression coefficient value is 2.424 or 24.24% with α value = 0.001 <0.05. The promotion has a positive and significant impact on interest in seeing Agro Purwosari by regression coefficient value 1.493 or 14.93% and value of α = 0.023 <0.05, Location has a positive but not significant effect on the interest in returning to Agro Purwosari withThe regression coefficient value is 0.963 or 96.3% and value of α = 0.175 > 0.05.